Answered

Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Identify the explicit function for the sequence in the table.

[tex]\[
\begin{tabular}{|c|c|}
\hline
$x$ & $y$ \\
\hline
1 & 7 \\
\hline
2 & 19 \\
\hline
3 & 31 \\
\hline
4 & 43 \\
\hline
5 & 55 \\
\hline
\end{tabular}
\][/tex]

A. [tex]$a(n)=7+(n-1) \cdot 12$[/tex]
B. [tex]$a(n)=12+(n-1) \cdot 7$[/tex]
C. [tex]$a(n)=7(n-1)$[/tex]
D. [tex]$a(n)=12(n-1)$[/tex]


Sagot :

To identify the explicit function for the sequence provided, let’s analyze the given values and formulate the rule step-by-step.

The sequence provided in the table is:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline 1 & 7 \\ \hline 2 & 19 \\ \hline 3 & 31 \\ \hline 4 & 43 \\ \hline 5 & 55 \\ \hline \end{array} \][/tex]

1. Check the differences between successive terms:
- [tex]\(19 - 7 = 12\)[/tex]
- [tex]\(31 - 19 = 12\)[/tex]
- [tex]\(43 - 31 = 12\)[/tex]
- [tex]\(55 - 43 = 12\)[/tex]

The difference between successive [tex]\( y \)[/tex]-values is consistent, indicating that the sequence is arithmetic with a common difference of 12.

2. Determine the general formula for the arithmetic sequence:
The general formula for an arithmetic sequence is:
[tex]\[ a(n) = a_1 + (n - 1) \cdot d \][/tex]
where:
- [tex]\(a_1\)[/tex] is the first term,
- [tex]\(d\)[/tex] is the common difference, and
- [tex]\(n\)[/tex] is the term number.

3. Identify the first term [tex]\(a_1\)[/tex]:
From the table, when [tex]\(x = 1\)[/tex],
[tex]\[ a_1 = 7 \][/tex]

4. Identify the common difference [tex]\(d\)[/tex]:
From the differences calculated earlier,
[tex]\[ d = 12 \][/tex]

5. Substitute [tex]\(a_1\)[/tex] and [tex]\(d\)[/tex] into the formula:
[tex]\[ a(n) = 7 + (n - 1) \cdot 12 \][/tex]

Hence, the explicit formula for the sequence is:
[tex]\[ a(n) = 7 + (n - 1) \cdot 12 \][/tex]

Reviewing the given options:
- [tex]\(A. a(n) = 7 + (n - 1) \cdot 12\)[/tex]
- [tex]\(B. a(n) = 12 + (n - 1) \cdot 7\)[/tex]
- [tex]\(C. a(n) = 7(n - 1)\)[/tex]
- [tex]\(D. a(n) = 12(n - 1)\)[/tex]

The correct formula corresponds to option [tex]\(A\)[/tex].

Therefore, the correct answer is:
[tex]\[ \boxed{A} \][/tex]